2014
DOI: 10.5713/ajas.2012.12425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Color on Energy Expenditure and Behavior in Broiler Chickens

Abstract: This study was conducted in order to investigate whether the presence of light or different colors of light would influence the energy expenditure and behavior of broiler chickens. Eight 8-week-old broiler chickens were adapted to a respiration chamber (Length, 28.5 cm; Height, 38.5 cm; Width, 44.0 cm) for one week prior to the initiation of the experiment. In experiment 1, energy expenditure and behavior of the chickens were analyzed in the presence or absence of light for four days. Chickens were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
3
11
0
2
Order By: Relevance
“…In broiler chickens, EE was found to be increased under bright light as compared to dim light, while behaviour was similar (Kim et al . ). Whether such effects of light on EE can also occur in man remains to be studied.…”
Section: Light and (Thermo)physiological Responsesmentioning
confidence: 97%
“…In broiler chickens, EE was found to be increased under bright light as compared to dim light, while behaviour was similar (Kim et al . ). Whether such effects of light on EE can also occur in man remains to be studied.…”
Section: Light and (Thermo)physiological Responsesmentioning
confidence: 97%
“…Over the past several decades, the light sources used in poultry husbandry are mainly incandescent or fluorescent lamps. Recently, light-emitting diodes (LED) are gradually replacing the incandescent or fluorescent lamps because they are much more energy efficient, provide adequate illumination, and improve growth performance of poultry (Rozenboim et al, 2004; Hassan et al, 2013; Kim et al, 2014; Riber et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The superiority of LEDs to other sources of light increases the use of this light source in poultry houses day by day [5] . Because perception levels of LED lamps at various wavelengths are different, a lot of researchs in broiler [1,9,25] and less in other poultry species [10,17,23] were determined to have different effects on performance in recent years, however, no information could be reached in partridge species. Investigatings in the present study showed that green LEDs increase feed intake of partridges significantly (Table 2).…”
Section: Discussionmentioning
confidence: 99%